CARVED STONES of the XV Century FROM the VILLAGES. KUBACHI WITH NAMES MADE THEM MASTERS - Mammaev, Misrihan Mamaevic (History, Archeology and Ethnography of the Caucasus, 2018)
The article describes the monuments of stone-cutting art of the XV century-six architectural details and one gravestone monument of highly artistic decoration of villages. Kubachi, on which are carved the names of the craftsmen who made them. Discusses the features of the decorative trim of carved stones. It is noted that not all master stone – cutters, who worked in the middle ages, tried to immortalize themselves, putting on their works inscriptions with their names. Only a few of them left their names on the work they performed. Therefore, a great number of carved stones, architectural details and tombstones from the village of Kubachi, as well as tombstones from neighbouring settlements – Calamarata, Ashty, Damage and other remain nameless.The tomb of the XV century described in the article, decorated at a high artistic level with calligraphically executed decorative Arabic inscription in the style of "blooming kufi" on the background of elegant floral ornament, is considered as an outstanding work of stone-cutting art, created in the middle ages in the villages. Kubachi. It is the only one among the gravestones studied by researchers to the present time, which presents the name of the master of stone – Carver, calligrapher and ornamentalist Jarak – a talented artist of decorative and applied art.
Keywords: Дагестан; Кубачи; резные камни; средние века; архитектурные детали; надмогильная стела; имена мастеров-камнерезов.